The Effect of Role Play Learning Model on Students' Critical Thinking Skills on The Blood Circulatory System in Elementary Schools - Wahyu Azhari; Nirwana Anas (MASI Mandiri Edukasi, 2025)
This study addresses the problem of low critical thinking skills among elementary school students, particularly in science learning about the circulatory system. The research aimed to examine the effectiveness of the role-playing learning model in improving fifth-grade students’ critical thinking abilities. A quasi-experimental design with a non-equivalent control group was applied, involving 50 students divided into experimental and control groups. Data were collected using pre-tests and post-tests, analyzed through normality, homogeneity, and independent t-tests with SPSS software. The results indicated that the experimental group, which engaged in role-playing activities, showed a significant increase in critical thinking scores from 48.80 to 82.80, compared to the control group, whose scores increased from 28.60 to 63.20. The t-test analysis confirmed a significant difference between the two groups. These findings suggest that role-playing is an effective instructional model to enhance students’ critical thinking skills, especially in understanding complex biological concepts such as the circulatory system.